The Nativeness of Breton Speakers and Their Erasure - Jouitteau, Mélanie (Studia Celtica Posnaniensia, 2019)
I discuss the nativeness of heritage speakers of Breton in the twentieth century. I present a syntactic test designed for Breton that sets apart its native speakers from its late learners, for whom Breton is a second language. Nativeness is revealed by a better tolerance to syntactic overload when sufficient linguistic stress is applied. Both heritage speakers of inherited Breton and early bilinguals whose linguistic input comes exclusively from school answer this test alike, which I take as a sign they are cognitively natives. The syntactic nativeness of children deprived of familial Breton input suggests there is many more young Breton natives among contemporary speakers than previously assumed. Taking stock of these results, I discuss the cultural erasure of Breton native speakers. I compare their cultural treatment with the figure of the ghost. I end by a discussion of the term new speaker.